IMPLEMENTASI SISTEM INFORMASI PEMERINTAH DAERAH (SIPD) KABUPATEN PROBOLINGGO - Sundari, Sundari; Woro Astuti, Sri Juni; Endarti, Esa Wahyu (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
The study will more clearly analyze the implementation of SIPD in Probolinggo District and identify the factors that become obstacles in planning SIPD in Probolinggo District which is carried out using a descriptive qualitative analysis approach. The results showed that the implementation of the Regional Government Information System (SIPD) platform in Probolinggo Regency was going well. Probolinggo Regency is carrying out a massive implementation of the SIPD platform accompanied by using companion applications and regional internal aplications; and the obstacles encountered include the SIPD application is still not able to meet the needs of information data collection so that it requires a companion application. The SIPD application does not yet provide a variety of data formats for printing reports, there are still gaps in data accuracy, and lack of outreach.